Strategi Bertahan Hidup Petani Kelapa Sawit Pada Saat Replanting Di Desa Ukui Dua Kecamatan Ukui Kabupaten Pelalawan Provinsi Riau - Apriaza, Rendy; Risdayati, Risdayati (Jurnal Ilmiah Wahana Pendidikan, 2026)
The replanting period for oil plam plantations presents significant challenges for farmers, particulary because they do not receive any harvest income in that time. This situation places them in an economic crisis that forces them to find various means of survival. In Ukui Dua Village, Ukui Subdistrict, Pelalawan Regency, this phenomenon is a real part of daily life of rural communities that rely on oil palm farming as their primary source of livehood. To understand how farmers navigate this difficult period, this stufi employs a qualitative approach with a case study method. Data were collected through in-depth interviews with seven oil pam farmers and two key informants, the head of the bukit potal village unit and the head of ukui dua village. The findings reveal three main strategies used by farmers, active strategies, passive strategies, and network-based strategies. Active strategies include part time work and small-scale businesses. Passive strategies involve cutting back on spending and minimizing consumption. Networt based strategies are pursued through family support and plasma partnerships. Among these, passive strategies emerged as the most dominant due to limited access to capital and non-agricultural skill